Exosome-related immune signatures and peripheral blood assays predict prognosis and immunotherapy response in hepatocellular carcinoma - Gao, Ruolian; Mi, Lili; Shi, Jianfei; Zhang, Meng; Duan, Xiaoling; Zhao, Man; Yin, Fei (Frontiers in Cell and Developmental Biology, 2026)
BackgroundExosomes are involved in cell-to-cell communication, and tumor-derived exosomes play an important role in the occurrence, development, and drug resistance of hepatocellular carcinoma (HCC) by regulating components in the tumor microenvironment (TME). However, the role of tumor-derived exosome-related immune (TDEI) genes in predicting HCC prognosis and immune therapy efficacy is not yet fully understood.MethodsThe exoRBase2.0, GSE181946, and The Cancer Genome Atlas (TCGA) databases were used to analyze TDEI genes. Cox regression and least absolute shrinkage and selection operator (Lasso) analyses were used to identify TDEI genes that are closely related to the overall survival (OS) of patients with HCC. Subsequently, a predictive model was constructed based on the TCGA database and validated in the International Cancer Genome Consortium (ICGC) database. A nomogram was developed to predict survival. Immune infiltration analysis was used to estimate changes in immune cells and stromal cells in the TME. Immunohistochemistry (IHC), Western blot, and qRT-PCR demonstrated the regulation of TDEI genes on the TME. Peripheral blood assays were used for predicting immunotherapy response.ResultsA combined prognostic model integrating S100A11 and PUSL1 expression with clinical characteristics was constructed, and it effectively predicted survival in HCC patients. S100A11 was associated with poorer immunotherapy efficacy. S100A11 regulated the TME by modulating interactions between cancer-associated fibroblasts (CAFs) and M2 macrophages. Experimental evidence demonstrated that S100A11 expression was associated with CAFs, M2 macrophage infiltration, and poorer progression-free survival (PFS). Interleukin-6 (IL-6), peripheral blood CD8+T cells, and prognostic nutritional index (PNI) can predict the response to immunotherapy.ConclusionIn this study, we identify a novel signature based on TDEI genes that has the potential to be a biomarker for predicting the prognosis and immunotherapy response for HCC. Peripheral blood tests can be used to predict the response to HCC immunotherapy. In our study, we provide an immunologic perspective for the development of precision therapy for HCC.